The influence of oral cimetidine administration on creatinine clearance in chilren with chronic renal failure: A preliminary study - Rosalina D Roeslani; Partini P Trihono; Sri Rezeki Harun (Indonesian Pediatric Society, 2005)
Background Serum creatinine and creatinine clearance are usedto assess glomerular filtration rate but have a major disadvantagesince a variable amount of creatinine is secreted in the proximaltubule. This may cause an unpredictable overestimation of GFR.Tubular creatinine secretion can be blocked by cimetidine throughcompetitive inhibition of cation transport in the proximal tubularluminal membrane.Objective Cimetidine administration might improve the reliabilityof creatinine as a marker of glomerular filtration.Methods A preliminary study with a one-group pretest-posttestdesign in 11 children with chronic renal failure. Serum cystatin Clevel as reference value was compared with creatinine clearancemeasured before and after oral ingestion of cimetidine. The doseof cimetidine was adjusted with the GFR using Schwartz formula.Statistical evaluation was done with the Wilcoxon signed rankstest.Result The mean creatinine clearance before cimetidine adminis-tration was 27.4 (SD 14.6) ml/minute/1.73 m 2 BSA, and decreasedafter cimetidine to 21.1 (SD 13,1) ml/minute/1.73 m 2 BSA (p=0.015).Conclusion Oral cimetidine was effective in inhibiting creatininetubular secretion. This study could not prove that cimetidine im-proves the accuracy of creatinine clearance